FUNGICIDAL POTENTIAL OF PURIFIED ALKALOIDS - SOLASODINE AND CAULOPHYLLUMINE-A FROM SOLANUM MAURITIANUM SCOP. AGAINST SOME PHYTOPATHOGENIC FUNGI - JAYA KUMAR K; GREESHMA GM; MURUGAN K (International Journal of Pharma and Bio Sciences, 2016)
Solanum mauritianum a shrub or small tree branched to form a rounded canopy. It is spineless and densely pubescent with sessile to long-stalked stellate hairs. The green berries ripen to yellow fruit which are globose. The fruit are borne in compact terminal clusters. The plant possesses the precursor for the synthesis of corticosteroid drugs from the unripe fruit or leaves of the plant. In this scenario, the present study aims the fungicidal potential of purified alkaloids - solasodine and caulophyllumine-A from Solanum mauritianum Scop. against selected phytopathogenic fungi such as Alternaria alternata, Fusarium oxysporum, Albugo candida, Rhizoctonia solani, and Cercospora arachidicola at concentrations of 0, 0.25, 0.5, 1, 1.5 and 2 and 3 (mg/l). Solasodine and caulophyllumine-A showed different degrees of fungicidal activity against the tested pathogens. When compared with the control, the highest fungicidal activity (MIC) was recorded for solasodine at a concentration of 0.15 mg/l against F. oxysporum while, caulophyllumine-A displayed antifungal property in the range 0.25 to 1mg/l. Alkaloids inhibited spore germination and mycelial growth significantly substantiating their fungicidal potentials. Extensive studies are warranted to trace the mode of action of the alkaloids as antifungal agent against the tested phytopathogenic fungi.